Analisis Pengaruh Brand Ambassador dan Online Customer Reviews terhadap Keputusan Pembelian Produk Somethinc di Marketplace Shopee - Hanasya Azizah Kirana; Donni Junipriansa (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study investigates the influence of brand ambassadors and online customer reviews on consumer purchasing decisions, with particular emphasis on Somethinc, a local beauty brand marketed through the Shopee e-commerce platform. Employing a quantitative methodology, data were gathered through structured surveys and questionnaires to explore patterns in consumer behavior and assess the interrelationships among the key variables. The dataset was analyzed using regression techniques facilitated by SPSS software. The findings reveal that brand ambassadors exert a statistically significant effect on consumer purchase decisions, while online customer reviews serve as pivotal informational cues that shape perceptions of product efficacy and, in turn, influence purchasing behavior. By focusing on a domestic cosmetic brand operating within a digital marketplace, this study advances the broader discourse on digital marketing strategies and highlights the critical roles of influencer endorsement and electronic word-of-mouth in shaping contemporary consumer decision-making processes. These findings offer practical implications for marketers seeking to optimize promotional efforts within the beauty sector.